Feeding frequency influences process performance and microbial community composition in anaerobic digesters treating steam exploded food waste. (December 2018) - Svensson, Kine; Paruch, Lisa; Gaby, John Christian; Linjordet, Roar
Highlights: Gas and methane production volumes were higher in the frequently fed reactor. Low methane yield linked to inhibition of β-oxidation and labile feedstock. Different microbial community in the frequently fed vs. once daily fed reactor. Abstract: In anaerobic digestion, studies of feeding frequency have produced conflicting results. Hence, the effect of feeding frequency on process variables and microbial community structure was investigated by comparing a laboratory-scale digester fed steam exploded food waste 10 times daily vs. one fed an equivalent amount once daily. The Frequently Fed Digester (FFD) produced on average 20% more methane and had lower effluent concentrations of long-chain fatty acids. Greater daily fluctuations in acetate, pH and biogas production rate could explain the lower specific methane yield and β-oxidation. Feeding frequency also influenced the microbial community whereby Tenericutes (42%) dominated in FFD but Firmicutes (31%) was most abundant in the Daily Fed Digester (DFD). Feeding frequency effects are therefore postulated to occur more often in digesters fed labile feedstocks at high organic loading rates.